Perancangan Pengalaman Pengguna Aplikasi Presensi dan Penilaian Akademik Santri menggunakan Metode User-Centered Design (Studi Kasus: Pondok Pesantren Anwarul Huda Malang) - Agus Nugroho; Eriq Muhammad Adams Jonemaro; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Anwarul Huda Islamic Boarding School is an educational institution located in Malang City, East Java with a total of 269 students. Based on the results of interviews with the management of the education division, Anwarul Huda Islamic Boarding School has problems in managing student data. The management of student data, such as the management of value data and attendance data is still done manually, so it is considered less effective and efficient. In the implementation of learning activities, students are also still often found cheating, namely there are still many students who commit attendance forgery. Based on these problems, the design of the user experience of the attendance application and the academic assessment of students was made. With this design, it is hoped that it can help the education division and the developer in creating a system that can help in managing student data. The method used in this study was to use user-centered design (UCD). The result of this study is a solution design in the form of a high-fidelity prototype which is then evaluated using usability testing. As for the results of the usability test, in the aspect of effectiveness, scores were obtained of 98.07% for admins, 98.33% for teachers, and 100% for students. The efficiency aspect obtained TBE scores of 0.12 goals/sec for admins, 0.103 goals/sec for teachers, and 0.17 goals/sec for students. The user satisfaction aspect obtained a system usability scale (SUS) score of 90 for admins, 77 for teachers, and 86.5 for students..